The Impact of environmental indicators (EIs) on the Market Value of Industrial Sector Companies: A Case Study of Baghdad Soft Drinks Company - Mohammed Neamah (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study looks at how Environmental Indicators, or EIs, affect the market value of industrial companies. To do this, it focuses on Baghdad Soft Drinks Company from 2018 to 2023. The reason for choosing this topic is that people around the world are getting more worried about environmental issues and how companies can help reduce the harm caused by industry to the environment. By exploring this, we can see how important it is for companies to consider their environmental impact and how it can impact their value in the market. The goal is to understand how environmental sustainability can influence the market value of industrial companies, using Baghdad Soft Drinks Company as a real-life example. The researcher looked at a range of environmental indicators, including emission levels, waste management, energy and water efficiency, and how well the company followed environmental standards. He also checked how much the company shared this information in its financial and sustainability reports, and how this affected the company's reputation among investors and stakeholders. By doing so, the researcher aimed to understand the impact of transparency on the company's image and reputation. This involved analyzing the company's disclosure practices and their role in shaping stakeholder perceptions. The researcher's focus on environmental indicators and disclosure practices allowed him to assess the company's environmental performance and its efforts to communicate this information to stakeholders. The study found some interesting things. It seems that how well a company does for the environment and how much it's worth on the market are connected. The Environmental Performance Index, or EPI, can explain about half of the changes in a company's market value. So, the researcher thinks that companies should focus on being more environmentally friendly. This can be done by using less energy and water, making less pollution, and recycling more. If companies do these things, it could help increase their market value over time. By taking care of the environment, companies can also take care of their bottom line. This is a win-win situation for both the company and the planet.When a company takes care of the environment and tells people about it, investors feel better about putting their money in. This can make the company's value go up. The study found that companies that are kind to the earth and follow sustainability rules are more likely to get ahead of their competitors and attract money from investors. By being responsible and transparent, businesses can gain trust and support from investors, which can lead to more financial opportunities and a stronger market position.